PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK DAN MOTIVASI BELAJAR SISWA DENGAN PEMBELAJARAN BERBASIS MASALAH DAN PEMBELAJARAN LANGSUNG - HIDAYATUL MAZIDAH HARAHAP (LP2MTBM MAKARIOZ, 2019)
The aim of this study was to examine: (1) Differences in the ability of solving mathematical students who received problem-based learning, better than students who received direct instruction, (2) The difference in learning motivation of students who received problem-based learning is better than students who acquire learning directly, (4) Pattern diverse responses of the students in solving problems on problem-based learning and hands-on learning. This research is a semi-experimental. The study population was a class vrn student. Data analysis was performed mathematical problem solving ability by analysis of covariance (Anacova), Questionnaire student motivation by Mann-Whitney test. The results showed that (1) There are differences in the results of mathematical problem solving abilities among the students who were given a problem-based learning with the students who were given direct instruction. (2) There is a difference in students' motivation is given a problem-based learning with the students who were given direct instruction. (3) Completion Process imposed students answer problem-based learning is better than direct